Zero: The Biography of a Dangerous Idea - Charles Seife (Rupa & Co, 2000)
This informative and easy-to-read book is the story of the people who battled over the meaning of the mysterious number - the scholars and mystics, the scientists and clergymen - who tried to understand zero.